Management of Schizophrenia in Ayurveda- A Case Report - KS, Adithya; R, Vinod (International Research Journal of Ayurveda & Yoga, 2022)
Schizophrenia is unarguably one of the most devastating mental illnesses. It often strikes early in life, and onset can signal the presence of an irreversible vulnerability toward psychosis that creates a lifetime of anguish and burden for patients and their loved ones. Symptoms of Schizophrenia are similar to that of Unmada mentioned in Ayurveda classics. This article deals with a case of Schizophrenia which was diagnosed as Kaphaja Unmada- Pithaanubandha according to diagnostic principles of Ayurveda. The patient is having general presentation that suggests the presence of negative symptoms, including signs such as communication difficulties, flat affect, limited emotion, social inactivity, low motivation, and retarded psychomotor activity along with some positive symptoms. She was administered with Dhaara, Snehapaana, Virechana, Vasthi and Nasya during 45 days of Inpatient management along with internal medications. The Positive and Negative Syndrome Scale (PANSS) was used to evaluate the efficacy of treatment. Total two assessments were carried out before treatment and after completion of 45 days of treatment. The results were promising and worth detailing, and the negative symptoms got complete relief on PANSS. Panchakarma procedures along with internal Ayurvedic medicines provided promising results for successful tapering of antipsychotic medication and also for better management of Schizophrenia along with improved life quality of the patient. The case report stresses the role of Ayurveda treatment modalities in managing similar psychiatric conditions